2007
DOI: 10.1002/anie.200604167
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yield Synthesis of Single‐Crystalline Gold Nano‐octahedra

Abstract: Pieces of eight: Single‐crystalline Au nano‐octahedra with well‐defined shape and tunable size can be synthesized by a modified polyol process. The octahedral Au nanocrystals have sharp corners and display optical properties that are sensitive to the crystal sizes and the truncation of the tips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
139
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(147 citation statements)
references
References 74 publications
5
139
0
3
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The primary step of this process involves the reduction of a metal salt by a polyol at an elevated temperature in the presence of a polymeric stabilizer such as poly(vinyl pyrrolidone) (PVP). Despite its success in controlling the shape of many noble metal nanocrystals, however, the major products are often restricted to cuboctahedrons or truncated cubes due to the fast reduction and growth rates associated with the strong reducing power of a polyol.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The primary step of this process involves the reduction of a metal salt by a polyol at an elevated temperature in the presence of a polymeric stabilizer such as poly(vinyl pyrrolidone) (PVP). Despite its success in controlling the shape of many noble metal nanocrystals, however, the major products are often restricted to cuboctahedrons or truncated cubes due to the fast reduction and growth rates associated with the strong reducing power of a polyol.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Indeed, the 54 nm octahedra with hollow features have an SPR maximum at 605 nm, which is 25 nm red-shifted from that of similar-sized solid Au octahedra ( Figure S4). (34) Many of the plasmonic applications of noble metal nanostructures rely on the ability to tailor the SPR of a particle to a desired wavelength. (35)(36)(37)(38) Other researchers have shown that the SPRs of hollow spherical gold nanoparticles are dependent on the size of their hollow cavity (3) and the thickness of the metal shell.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Among various MNPs, gold nanoparticles (GNPs) are particularly interesting due to their remarkable size-and shapedependant optical and catalytic properties and numerous potential applications. [11,[14][15][16][17][18] Consequently, several methods are available in the literature to produce GNPs ranging from rods, [9,19] cubes/polyhedra, [20][21][22][23] multipods, [14,24] to triangular nanoplates [4,25] and nanoprisms. [26] Conventional approaches for the production of anisotropic GNPs rely on the availability of surfactants, polymeric or biological templates that preferentially adsorb on specific crystallographic facets and hence modify the relative growth rates of the facets.…”
Section: Introductionmentioning
confidence: 99%